The Value Gap: How Gender, Generation, Personality, and Politics Shape the Values of American University Students - Rausch, Zachary M. (Journal of Open Inquiry in the Behavioral Sciences, 2025)
Greg Lukianoff and Jonathan Haidt, in their book, The Coddling of the American Mind (2018), portrayed current undergraduate American college students (most of whom are in the generation Gen Z: 1995 - 2013) as valuing emotional well-being and the advancement of social justice goals above traditional academic values such as academic freedom and the pursuit of truth. We investigated whether this value discrepancy exists among 574 American university students by exploring the prioritization of five different academic values (academic freedom, advancing knowledge, academic rigor, social justice, and emotional well-being). We also explored how gender, generation, personality, major, and conservatism predict each academic value. Generational differences were present, with Gen Z students emphasizing emotional well-being and de-emphasising academic rigor. Males scored higher on measures of academic freedom and advancing knowledge, while lower on social justice and emotional well-being compared to females. Political conservatism was the strongest predictor for social justice scores, with increased liberal attitudes predicting higher scores on social justice. Emotional stability positively predicted advancing knowledge, while negatively predicting emotional well-being. Agreeableness positively predicted emotional well-being, while negatively predicting advancing knowledge. We ultimately argue that gender is a crucial, underestimated explanatory factor of the value orientations of American college students.10.58408/issn.2992-9253.2023.01.01.00000001